A dual-carbon-anchoring strategy to fabricate flexible LiMn2O4 cathode for advanced lithium-ion batteries with high areal capacity. (January 2020) - Yu, Xiaoliang; Deng, Jiaojiao; Yang, Xin; Li, Jia; Huang, Zheng-Hong; Li, Baohua; Kang, Feiyu
Abstract: Lithium transition metal oxides (LTMOs) are important cathode materials in lithium-ion batteries (LIBs). Constructing the robust hybrid of LTMO-flexible substrate is of great significance for developing advanced flexible LIBs. However, currently reported flat noble metal-based flexible cathodes are cost-expensive and show quite low areal capacities. Developing low-cost and nanostructured flexible substrates for LTMO cathodes is highly desirable but still rarely reported. Particularly challenging is preventing flexible substrate corrosion and mitigating/eliminating the severe ion migration at interface during necessary high-temperature annealing process. Herein, carbon nanofibers (CNFs) with truncated conical graphene layers are carefully chosen as flexible substrates for the growth of ultrasmall LiMn2 O4 nanocrystals. The highly graphitic structure enables good high-temperature oxidation resistance. The plenty of exposed graphitic edge planes afford unexpected strong anchoring of LiMn2 O4, evidenced by both experimental results and theoretical calculations. Moreover, an amorphous carbon layer is simultaneously introduced and coated on LiMn2 O4 nanocrystals, which provides another strong outer anchoring like a 'cargo net'. Such dual-carbon-anchoring strategy help produce a 1D LiMn2 O4 -nanocarbon hybrid with robust interface. As LIB cathode, it owns fast electron conduction, smooth Li + transportation, good electrochemical stability and especially superior mechanical flexibility, thus enabling a high areal mass loading of 17.7 mg cm -2 . The corresponding fabricated flexible LiMn2 O4 /CNF@C//CNF full cell exhibits a high areal capacity of 2.01 mAh cm -2 as well as good rate capability and cycling stability. Graphical abstract: Image 1 Highlights: Graphitic carbon nanofibers (CNFs) are used as flexible substrate for LiMn2 O4 cathode. The exposed graphitic edge planes and amorphous carbon layer provide strong inner and outer anchoring respectively. The dual-carbon-anchoring strategy help produce a 1D LiMn2 O4 -nanocarbon hybrid with robust interface. As-fabricated flexible LiMn2 O4 cathode exhibits quite high areal capacity, good rate capability and cycling stability.